Analisis Kesulitan Mahasiswa dalam Mengembangkan Lembar Kerja Siswa dan Media Pembelajaran Interaktif Matematika - Muhammad Ridlo Yuwono; M. Wahid Syaifuddin; Yuliana Yuliana (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: This study aims to analyze the difficulties of students in developing student worksheets (LKS) and interactive mathematics learning media. This research is descriptive qualitative research with a case study approach. The subjects of this study were students of the Mathematics Education Study Program at Widya Dharma University, Klaten. The data collection method used in this research is documentation, observation, and interviews. Method triangulation techniques are used to obtain valid data by comparing the results of observations with the results of interviews. The data analysis process in this study was carried out based on the model of Miles, which includes data condensation, data presentation, and drawing conclusions. The results of this study show that students experience difficulties in developing worksheets and interactive learning media. The types of difficulties are (1) difficulty in arranging findings or formula construction on certain materials, (2) difficulty in compiling worksheets and learning media that require students to provide varied responses, (3) difficulties in developing contextual and challenging initial problems and (4) difficulty in constructing apperception.